Class 1 Integrons and Associated Gene Cassettes in Multidrug Resistant Acinetobacter baumannii from Southwest Nigeria: A Tertiary-Hospitals Study. - Ike, Williams; A. Adeniyi, Bolanle; E. Peters, Joseph (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
Background: Flooded soil is a significant agronomic problem because most plants do not tolerate excess water in the soil. Yenagoa, Bayelsa State is characterized by seasonal flooding that often engulf cultivated soils. This study was conducted to assess the response of Phaseolus vulgaris to flooded soil condition in the study area. Methods: Viable seeds of the test crop were sterilized and sown in soils of Site A (control) and B (flooded soil) in rows. The research work was planned such that, the P. vulgaris seedlings were established up to one (1) month before the area (Site B) was flooded. Plant growth parameters such as plant height, leaf number, dry weight, nitrogen, phosphorus and potassium contents were examined. Results: P. vulgaris exhibited moderate wilting and chlorosis during the first week of exposure to flood condition. The severity of wilting and chlorosis increased with increase in the duration of the stress condition. Other morphological characteristics observed were retarded growth, dropping of leaves, decrease leaf number, and reduced leaf size during the second and third week of exposure to flood condition, and death of the entire plant at the fourth week of study. The leaf number and dry weight of the crop decreased with increase in the duration of exposure to flood condition with values comparatively lower than that of the control Conclusion: This study showed that P. vulgaris was susceptible to flooded soil.